Towards Racing Gamification with Natural Interface for post stroke Rehabilitation - Ahmad Hoirul Basori; Alaa Omran Almagrabi (Universitas Sriwijaya, 2017)
Stroke patient basically suffer from limited movement, they cannot control their balance very well, therefore the therapy that involve repetitive motion, harmonization and stability workout should be applied to them. The invention of Kinect has lead people to applied this device as a tool for recovering patient from stroke because its capability on tracking the skeletal of human body. Racing Game is very popular among the adults, elderly and even kids, the rule it’s quite simple and understandable. The combination between the racing game and natural interface will lead to innovative application which is potential to be used as home therapy for post stroke patient. User will be required to move some parts of their body such as both hand, arm, head and even shoulder. The body tracking is provided by depth camera that can capture and interpret human body gesture recognition to be used as interaction command. The human skeleton will be displayed onto screen to control the car in the game and the result of racing will be synchronized with user excitement which is recorded through Kinect video.